The changing role of the secretarial profession / Halifah Abdul Rahman - Abdul Rahman, Halifah (Kolej Cempaka Kenanga, UiTM Shah Alam, 2000)
In as early as the 14th century or even earlier, secretarial job titles frequently included "personal" or "private". Men continued to dominate the secretarial field until the late 18th century. After the invention of the writing machine, many women entered the office workforce for various clerical roles. Women came to the rescue during the industrial period at the turn of the century, where business offices faced a paperwork crisis. Women adapted well to new technologies such as the adding and calculating machines, telephones, and typewriters. Many women held positions as secretaries. The demand for secretaries was so great it could not meet the supply. By this time women dominated the office workforce.